Pemberdayaan Kelompok Pembudidaya Ikan Desa Pakowa Bunta dengan Menggunakan Ekstrak Daun Sirih (Piper betle L.) dalam Pakan pada Budidaya Ikan Nila Sistem Bioflok: Empowerment of the Pakowa Bunta Village Fish Cultivator Group Using Betel Leaf Extract (Piper betle L.) in Feed in Biofloc System Tilapia Cultivation - Agustina, Sri Sukari; Wuniarto, Erwin; Botutihe, Nuratni; Saputra, Dicki Alif; Hamsun, Zulfikar; Usman, Ramadhani; Balau, Fitriani; Fajriansyah, Rian (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Pakowa Bunta Village is one of the villages in Nuhon District, Banggai Regency, physically it is a lowland area located on the coastline. The large area of tilapia ponds in Pakowa Bunta Village and the suboptimal management of tilapia cultivation have caused many tilapia fish to die. The repeated failure of cultivation in the traditional system of tilapia cultivation in Pakowa Bunta Village requires the transfer of innovative fish cultivation technology from the traditional system to the biofloc system. This community service activity aims to improve the skills and knowledge of fish cultivator groups regarding biofloc system fish cultivation and increase the economic income of fish cultivators in Pakowa Bunta Village. The approach used to resolve partner problems in this activity is the Community Development method, which is oriented towards developing community empowerment by making the community the subject and object of development and direct involvement in various service activities. The final result achieved from this community service activity is an increase in the skills of the fish cultivator group in innovating tilapia cultivation technology using a biofloc system that is modified by using betel leaf extract in the feed given to tilapia, resulting in an increase in tilapia production and an increase in the community's economic income of fish farmers.